2016
DOI: 10.3109/03009742.2016.1158314
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay of pyogenic vertebral osteomyelitis and its associated factors

Abstract: Despite easier access to MRI, the DD for PVO remains long. One shortening factor is a high CRP value, which could be a useful diagnostic tool in case of back pain. Anti-inflammatory drugs seem to have no impact on DD and severity at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…We speculate, physicians may delay obtaining blood cultures in patients with lower CRP level, similar to delay in diagnosis of vertebral osteomyelitis related to lower CRP level. [ 20 ] Physicians may attribute either viral infections or some other non-bacterial causes in patients with the lower CRP level. Moreover, our research (data not shown in the part of Results) showed that patients with IE attributed to streptococcus species had lower CRP levels.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate, physicians may delay obtaining blood cultures in patients with lower CRP level, similar to delay in diagnosis of vertebral osteomyelitis related to lower CRP level. [ 20 ] Physicians may attribute either viral infections or some other non-bacterial causes in patients with the lower CRP level. Moreover, our research (data not shown in the part of Results) showed that patients with IE attributed to streptococcus species had lower CRP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytosis is not necessarily present, whereas increased CRP is seen in 90%-98% of cases (4, e15). Jean et al showed that an increased CRP can shorten the time to diagnosis compared with other laboratory parameters (9). The procalcitonin (PCT) level plays a minor role as a parameter of sepsis in the primary diagnosis of spondylodiscitis, is more cost-intensive than CRP determination, and is not suitable as a follow-up parameter (11).…”
Section: Laboratory and Microbiological Testsmentioning
confidence: 99%
“…The remaining authors state that they have no conflict of interests. High CRP (56 days shorter) or positive blood culture (60 days shorter) are associated with a shorter diagnostic delay (2017) (9) Diabetes as a predisposing factor (2009) (10)…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…Symptoms can also be misattributed to unremitting back pain from degenerative spinal disorders. As a result, the diagnosis of spinal infections can often be delayed and result in severe neurological complications [9]. Physical examination may reveal localized spinal tenderness over involved regions with limited range of motion.…”
Section: Clinical Evaluationmentioning
confidence: 99%